An Update of the Effect of Far Infrared Therapy on Arteriovenous Access in End-stage Renal Disease Patients. Issue 4 (July 2016) - Chen, Chun-Fan; Yang, Wu-Chang; Lin, Chih-Ching
The life qualities of end-stage renal disease (ESRD) patients rely largely on adequate dialysis, and a well-functioning vascular access is indispensable for high quality hemodialysis. Despite the advancement of surgical skills and the optimal maintenance of arteriovenous fistula (AVF), malfunction of AVF is still frequently encountered and has great impact on the life of ESRD patients. Several medical, mechanical and genetic prognostic factors are documented to affect the patency of AVF and arteriovenous graft (AVG). Heme oxygenase-1 (HO-1) is one of the genetic factors reported to play a role in cardiovascular disease and the patency of vascular access. Far infrared (FIR), a novel therapeutic modality, can not only conduct heat energy to AVF but also stimulate the non-thermal reactions mediated by HO-1. The use of FIR therapy significantly enhances the primary patency rate and maturation of AVF with fewer unfavorable adverse effects, and also achieves higher post-angioplasty patency rate for AVG. The only limitation in proving the effectiveness of FIR therapy in enhancing patency of AVF is that all the studies were conducted in Chinese people in Taiwan and thus, there is a lack of evidence and experience in people of other ethnicities.